Tuning Contact Barrier Height between Metals and MoS2 Monolayer through Interface Engineering. Issue 12 (4th April 2017) - Chai, Jian Wei; Yang, Ming; Callsen, Martin; Zhou, Jun; Yang, Tong; Zhang, Zheng; Pan, Ji Sheng; Chi, Dong Zhi; Feng, Yuan Ping; Wang, Shi Jie
Abstract : Creating an electrical contact to 2D semiconductors with low resistance is a challenging task. In this study, by combining photoemission spectroscopy measurements and first‐principles calculations, it has been shown that a significant interfacial reaction occurring between the high work function metal Ni and an MoS2 monolayer leads to a metallic MoS2 monolayer and a high contact barrier height. By introducing an additional MoS2 layer as a buffer layer, both of these effects can be remedied, resulting in the desired semiconducting channel layer and a reduced contact barrier height. Further applying this strategy to the low work function metal Ti interfaced with an MoS2 monolayer, the contact barrier height can be decreased to about 0.29 eV. The results of this study provide an improved understanding of the interfacial interaction between metals and 2D semiconductors. In addition, a technically less demanding way to tune the contact barrier height is demonstrated. Abstract : Based on first‐principles calculations, it has been shown that the interaction between metals and MoS2 monolayer can be tuned by interface engineering. By using an additional MoS2 layer as a buffer layer, the strong interfacial interaction is reduced, which results in a significantly lowered Schottky barrier height and a semiconducting MoS2 channel layer.